2019
DOI: 10.1111/jsr.12905
|View full text |Cite
|
Sign up to set email alerts
|

Home versus laboratory assessments of melatonin production and melatonin onset in young adults complaining of a delayed sleep schedule

Abstract: Recent evidence points toward an association between higher non‐visual sensitivity to light and a later circadian phase in young adults complaining of a delayed sleep schedule. Light exposure in the evening may therefore induce a larger suppression of melatonin production in these individuals, which might: (a) bias home estimates of melatonin onset; and (b) decrease sleep propensity at bedtime. In this study, we compared home and laboratory melatonin onsets and production in sleep‐delayed and control participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(52 reference statements)
0
2
1
Order By: Relevance
“…A third mechanism suggests that light emission from the screens of electronic media devices could interfere with the circadian rhythm by suppressing physiological nocturnal secretion of the sleep-promoting hormone melatonin. 17 Furthermore, our study, did not show a significant relationship between the use of screens and the duration of sleep on weekends. It is possible that on weekends, the use of screens has more influence on bedtime which can be compensated for by waking up later.…”
Section: Discussioncontrasting
confidence: 58%
“…A third mechanism suggests that light emission from the screens of electronic media devices could interfere with the circadian rhythm by suppressing physiological nocturnal secretion of the sleep-promoting hormone melatonin. 17 Furthermore, our study, did not show a significant relationship between the use of screens and the duration of sleep on weekends. It is possible that on weekends, the use of screens has more influence on bedtime which can be compensated for by waking up later.…”
Section: Discussioncontrasting
confidence: 58%
“…The relationship between chronotype and sleep phenotype is less well-understood. Eveningness is associated with delayed sleep onset, as measured by both objective and subjective methods (Yadav and Singh, 2014;Van der Maren et al, 2018;Moderie et al, 2019). Evening orientation has also been associated with shorter sleep duration on work days and poorer sleep quality (Roepke and Duffy, 2010;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the fourth and last part of a larger research project and more details on subjects' selection can be found in the previous publications. [25][26][27] Subjects' characteristics are summarized in Table 1.…”
Section: Participants and Methods Participantsmentioning
confidence: 99%